2008
DOI: 10.1002/zaac.200700552
|View full text |Cite
|
Sign up to set email alerts
|

Rare Earth Metal‐Rich Magnesium Compounds RE4IrMg (RE = Y, La, Pr, Nd, Sm, Gd, Tb, Dy) and RE23Ir7Mg4 (RE = La, Ce, Pr, Nd)

Abstract: The rare earth metalϪrich compounds RE 4 IrMg (RE ϭ Y, La, Pr, Nd, Sm, Gd, Tb, Dy) and RE 23 Ir 7 Mg 4 (RE ϭ La, Ce, Pr, Nd) were synthesized from the elements in sealed tantalum tubes in an induction furnace. Several structures were investigated on the basis of X-ray single crystal diffraction: P6 3 mc, Z ϭ 2, a ϭ 1001.2(7), c ϭ 2257.2(5) pm, wR2 ϭ 0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Such segregations are not unusual in metal‐rich compounds. Besides the Cd 2 pairs reported herein we already observed Cd 4 tetrahedra in the Gd 4 RhIn type29 series RE 4 T Cd,9 in the Pr 23 Ir 7 Mg 4 type30 series RE 23 T 7 Cd 4 9 and the new structure type La 15 Rh 5 Cd 2 31. Pair formation occurs also for the indium atoms in the rare earth metal‐rich compounds RE 14 T 3 In 3 ( T = Co, Ni, Rh).…”
Section: Resultssupporting
confidence: 64%
“…Such segregations are not unusual in metal‐rich compounds. Besides the Cd 2 pairs reported herein we already observed Cd 4 tetrahedra in the Gd 4 RhIn type29 series RE 4 T Cd,9 in the Pr 23 Ir 7 Mg 4 type30 series RE 23 T 7 Cd 4 9 and the new structure type La 15 Rh 5 Cd 2 31. Pair formation occurs also for the indium atoms in the rare earth metal‐rich compounds RE 14 T 3 In 3 ( T = Co, Ni, Rh).…”
Section: Resultssupporting
confidence: 64%
“…The Dy-containing sample was selected for closer inspection by metallographic analysis, which provided evidence for the existence of a new ternary phase (Figure S1). Analysis of the powder XRD pattern of this sample suggested that this phase probably adopts either the hexagonal Pr 23 Ir 7 Mg 4 - or Yb 23 Cu 7 Mg 4 -type structure, so its precise chemical formula would be Dy 23 Ni 7 In 4 . With this information at hand, the powder XRD patterns for the other samples were re-examined to show that the ternary phase RE 23 Ni 7 In 4 also forms for RE = Gd and Tb, but not for RE = Y and Ho.…”
Section: Resultsmentioning
confidence: 97%
“…The structural assignment for RE 23 Ni 7 In 4 was reasoned by searching for examples of compounds with similar chemical compositions within RE–T–X systems, where X are s-block, late d-block, or p-block element (e.g., Li, Mg, Cd, Zn, Al, Ga). Initially, the noncentrosymmetric Pr 23 Ir 7 Mg 4 -type structure (space group P 6 3 mc ) was assumed on the basis of its prevalence in Pearson’s Crystal Data, with nearly 60 representatives known. Moreover, it is adopted by Ce 23 Ru 7 In 4 , which is closely related in chemical composition to RE 23 Ni 7 In 4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The crystal chemistry of rare earth ( RE )‐rich phases in the ternary systems RE ‐ T ‐ X ( T =electron‐rich transition metal; X =Mg, Cd, Al, In) is dominated by a few structure types with a larger number of representatives, [1] namely Gd 4 RhIn, [2,3] Pr 23 Ir 7 Mg 4 , [4] Pr 15 Rh 5 Cd 2 , [5] Y 10 RuCd 3 , [6] Lu 14 Co 3 In 3 , [7,8] and Ho 6 Co 2 Ga, [9] besides some peculiar structure types. The high rare‐earth content of these different compounds leads to some common structural motifs.…”
Section: Introductionmentioning
confidence: 99%